2019
DOI: 10.1136/bmjqs-2019-009396
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with inappropriate use of emergency departments: findings from a cross-sectional national study in France

Abstract: BackgroundInappropriate visits to emergency departments (EDs) could represent from 20% to 40% of all visits. Inappropriate use is a burden on healthcare costs and increases the risk of ED overcrowding. The aim of this study was to explore socioeconomic and geographical determinants of inappropriate ED use in France.MethodThe French Emergency Survey was a nationwide cross-sectional survey conducted on June 11 2013, simultaneously in all EDs in France and covered characteristics of patients, EDs and counties. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
73
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(80 citation statements)
references
References 66 publications
1
73
2
1
Order By: Relevance
“…Moreover, it is very common to observe in our hospital, during the first months of the year, ED overcrowding, partially due to the winter virus season and, in part, to inappropriateness of access for non-urgent visits [ 13 , 14 ]. On this subject, some authors suggested that around 20–30% of ED visits may be defined as inappropriate, probably due to some critical issues inside national health systems, such as lack of primary care centers and low collaboration with general practitioners (GPs) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is very common to observe in our hospital, during the first months of the year, ED overcrowding, partially due to the winter virus season and, in part, to inappropriateness of access for non-urgent visits [ 13 , 14 ]. On this subject, some authors suggested that around 20–30% of ED visits may be defined as inappropriate, probably due to some critical issues inside national health systems, such as lack of primary care centers and low collaboration with general practitioners (GPs) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…While providers voiced frustrations with certain types of ED visits, which some have described as inappropriate,33 34 providers were also aware of reasons underlying some of these visits. Socioeconomic vulnerabilities, barriers to outpatient care, and limited community-based services lead many to the ED for services that the ED is ill-equipped to provide (eg, psychiatric or substance use services) or not designed to provide (eg, food or shelter), or for services that are arguably unnecessary and expensive for the ED to provide (eg, treatment for seasonal colds) 33 34…”
Section: Discussionmentioning
confidence: 99%
“…14 Disease-related anxiety, feelings of safety, and familiarity with the hospital setting are also factors influencing the patients and their family’s decision to seek urgent medical help at the EOL. 15,16 The integration of PC has been reported to make avoidable ED visits; in this work, only 8.4% of patients had been referred to PC; nevertheless, no statistically significant differences were found in the number of visits to ED in the last month of life.…”
Section: Discussionmentioning
confidence: 55%